2012
DOI: 10.1007/s13312-013-0119-8
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin nomogram for prediction of significant hyperbilirubinemia in North Indian neonates

Abstract: Hour-specific bilirubin nomogram and STB measurement can be used for predicting subsequent need of phototherapy. Further studies are needed to validate performance of risk demarcation zones defined in this hour-specific bilirubin nomogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…This is consistent with previous studies reported in the literature. 6,9,11 The clinical risk factors such as GA and loss of birth weight in percentage are very good predictors of SHB found in the present study. Studies have suggested that predischarge STB with GA could be a superior predictor for SHB.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is consistent with previous studies reported in the literature. 6,9,11 The clinical risk factors such as GA and loss of birth weight in percentage are very good predictors of SHB found in the present study. Studies have suggested that predischarge STB with GA could be a superior predictor for SHB.…”
Section: Discussionsupporting
confidence: 72%
“…8 Pathak, et al also showed that STB and hour-specific bilirubin nomogram could be used for forecast subsequent require of phototherapy. 9 When considered early in the life (at 18-24 hours after birth), STB, using a cut-off value of >3.99mg/dl, could also predict later SHB. 10 However, none of the studies on pre-discharge cut-off value of STB in Indian infants and also none of discovered the combination of STB and clinical risk factors for predischarge assessment in term newborns.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, before neonates are discharged from birth hospital those at risk of developing high bilirubin levels need to be identified. 7 The purpose of the study is to determine the risk factors associated with development of significant hyperbilirubinemia in newborns, so that we can keep a close follow up of babies who have the risk factors of developing significant hyperbilirubinemia in the future. Also the study is intended to determine the treatment modality for significant hyperbilirubinemia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we optimized the conditions to maximize the lipase production and evaluated the solvent stability of lipase using various organic solvents. B. licheniformis has been reported to produce a variety of extracellular enzymes such as protease [14], amylase [15], lipase [16], and xylanase [17]. However, no reports are available on an organic solvent-stable lipase from a solvent-tolerant strain of B. licheniformis.…”
Section: Introductionmentioning
confidence: 99%